2019
DOI: 10.7554/elife.45306
|View full text |Cite
|
Sign up to set email alerts
|

Light-at-night exposure affects brain development through pineal allopregnanolone-dependent mechanisms

Abstract: The molecular mechanisms by which environmental light conditions affect cerebellar development are incompletely understood. We showed that circadian disruption by light-at-night induced Purkinje cell death through pineal allopregnanolone (ALLO) activity during early life in chicks. Light-at-night caused the loss of diurnal variation of pineal ALLO synthesis during early life and led to cerebellar Purkinje cell death, which was suppressed by a daily injection of ALLO. The loss of diurnal variation of pineal ALL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 65 publications
(126 reference statements)
0
20
0
Order By: Relevance
“…To investigate whether light conditions are involved in pineal allopregnanolone synthesis in juvenile birds, the birds were incubated under either a 12 hours light‐12 hours dark (LD) cycle or a 12 hours light‐12 hours dark cycle followed by exposure to light for 1 hour during the dark period (light‐at‐night). It was found the allopregnanolone concentration and synthesis are higher during the dark period in the pineal glands of LD birds than during the dark period in the pineal glands of light‐at‐night birds (Figure ). It was further found that Purkinje cell numbers are decreased in the cerebellum by light‐at‐night during (Figure ).…”
Section: Mode Of Action Of and Functional Significance Of Pineal Allomentioning
confidence: 94%
See 4 more Smart Citations
“…To investigate whether light conditions are involved in pineal allopregnanolone synthesis in juvenile birds, the birds were incubated under either a 12 hours light‐12 hours dark (LD) cycle or a 12 hours light‐12 hours dark cycle followed by exposure to light for 1 hour during the dark period (light‐at‐night). It was found the allopregnanolone concentration and synthesis are higher during the dark period in the pineal glands of LD birds than during the dark period in the pineal glands of light‐at‐night birds (Figure ). It was further found that Purkinje cell numbers are decreased in the cerebellum by light‐at‐night during (Figure ).…”
Section: Mode Of Action Of and Functional Significance Of Pineal Allomentioning
confidence: 94%
“…It was found the allopregnanolone concentration and synthesis are higher during the dark period in the pineal glands of LD birds than during the dark period in the pineal glands of light‐at‐night birds (Figure ). It was further found that Purkinje cell numbers are decreased in the cerebellum by light‐at‐night during (Figure ). It is, therefore, considered that pineal allopregnanolone contributes as an important internal factor depending on the environmental light conditions to affect cerebellar development in vertebrates.…”
Section: Mode Of Action Of and Functional Significance Of Pineal Allomentioning
confidence: 94%
See 3 more Smart Citations